Effectiveness Of The Question Answer Method With Learning Media Variations For Improve The Achievement Of Ppkn In Sd Negeri 29 Teratak Panas - Eli Marnis (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: a. How to improve the learning outcomes of PPKN on the students of grade V SD N 29 Terakak Heat by using Q & A method with variation of learning media in January 2015? b. Steps taken in improving achievement and motivation to learn PPKN? Research Subject (sample): Student Class V 3) Subject: Civics 4) Media used a) Essays that tell one's ideals (Ideology Concept Planting) b) Strong house, building, or building image (National Basic Concept Planting c) Worksheet d) National Songs 4) Semester / Lesson Year: 2015 5) Circle. physical school: Rural 6) Socio-economic background of lower middle class parents 7) Ability of students: moderate 8) Student learning motivation: low This research is a classroom action research, therefore this research is not planned from the beginning, but only planned after the result of teaching learning process felt the problem (less satisfy). Preparatory steps after being exposed to problems that need to be solved through this TOD are: 1) conduct a preliminary study by reflection, ie discussion with some related teachers (especially research partners) with problems found 2) develop action plan, including: a) make a lesson plan b) make an agreement with the research partner. The number of cycles in this TOD is not predetermined, but is strongly influenced by the data obtained and the results of its analysis. If the data obtained is satisfactory to answer the research problem, then the research cycle is considered complete Data collection techniques in this study were obtained through obeservation and field data records, interviews, test results and record of reflection / discussion results conducted by researchers and research partners. Determination of such techniques is based on the availability of facilities and infrastructure and capabilities of researchers and research partners. Based on the results of the implementation of classroom action research on the application of Question Answer Methods on the students of class V SDN 29 Terakak Heat in Civics subjects that lasted for 3 cycles of research can be concluded: 1. During the PTK, the effort of applying the Q FAQ method variation of instructional media has been managed with good. 2. Learning activities with Q & A method with well-managed media variation proved effective enough to improve student learning outcomes. 3. Learning media to make essays and drawings that are varied with the Q & A method is effective enough to convey the material of Pancasila as the Basic of State and as the State Ideology. 4. Hypothesis of action that states "if the effort of applying the Q & A method of variations of learning media can run effectivly, then the student learning outcomes will increase" is acceptable.